Optimalisasi Kalsium Karbonat Dari Cangkang Telur Untuk Produksi Pasta Komposit - Warsy Warsy; St Chadijah; Wa Ode Rustiah (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2016)
Egg shell is a household waste which can be used to produce a composite paste, as it contains around 90% calsium carbonate (CaCO3) as the main composition. This research aims to determine the optimum weight of egg shell powder in composite paste production. This research is conducted by determining the calsium carbonate content beforehand by EDTA titration and the determination of the contain of calsium by using atomic absorption spectroscopy (AAS), then the determination of the optimum weight of shell powder by varying the shell powder and baking soda. The results of the research that has been done that the content of calsium carbonate in the shell of eggs was 92,57% and calsium at 28%. While the optimum weight for the shell powder manufacture composite paste which is 3 grams with a ratio of 3,0 (Ca) : 7,0 (BS), in which the pH obtained is 9. This is in a accordance by SNI that the pH value of the composite paste is 4,5–10,5 and is semisolid form.